Edukasi Gizi Seimbang untuk Meningkatkan Kesehatan Remaja Di SMPN 14 Padang - Indah Wulandari; Tazkia Putri Kagami; Syahrial; Jeallyza Muthia Azra (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2025)
Adolescents are vulnerable to nutrition-related problems due to unhealthy eating patterns and limited nutrition literacy. Strengthening nutrition knowledge through engaging, interactive, and participatory approaches is essential to support healthier decision-making. This community service program aimed to improve junior high school students’ understanding of balanced nutrition through a participatory education model integrating creative media and interactive games. The intervention was conducted at junior high school 14 Padang in September 2025 involving 57 ninth-grade students. Educational activities included a structured presentation, visual materials such as posters and leaflets, and interactive nutrition games based on the “Tumpeng Gizi Seimbang” and “Isi Piringku” concepts. Knowledge assessment used pre-test and post-test questionnaires, and data were analyzed using paired sample t-test. Results showed a significant improvement in students’ knowledge (p = 0.001), with the proportion categorized as having high knowledge increasing from 75.4% to 87.7%. These findings highlight the effectiveness of combining participatory strategies with creative media and interactive activities in enhancing adolescents’ understanding of balanced nutrition. The implications of this program indicate that, when implemented consistently and supported by the school environment, participatory approaches may contribute to more sustained improvements in students’ nutrition-related awareness. Schools are encouraged to incorporate interactive media in health education and conduct periodic follow-up activities to maintain knowledge retention.